Comparison of emissions depending on the type of vehicle engine - Rievaj, Vladimír (Logistics and sustainable transport, 2019)
Road transport is showing growth in the period of globalization. Its task is to transport cargo as well as people to the required location within the shortest possible time and at the lowest price. Thus, road transport plays a crucial role in enabling the globalization to be developed and improved. However, the internal combustion engine hat prevail among the vehicles of freight and passenger transport are the producers of gaseous emissions from the exhaust gases. Many developed countries of the world has committed themselves, inter alia also trough the Paris Agreement, to reduce global warming, and thus to reduce the production of harmful gaseous emissions. The result is the endeavour to replace the internal combustion engine vehicles that burn carbon fuels with the vehicles powered by electric motors consuming electric energy. The reason of such trying claims that road transport using the internal combustion engine vehicles is environmentally aggressive, and the problem would not be solved by implementation of the vehicles with electric motors. Such claim is based on the fact that an electric car does not produce any of primary emissions. From an overall perspective, it is also necessary to take into account secondary emissions that are produced during the electric energy production by which is the vehicle with electric motor powered. The purpose of this article is to assume the possibility of reducing global pollution by replacing the internal combustion engine vehicles with the vehicles powered by electric motors in dependence with producing the emissions during the production of electric energy.
Keywords: electric energy; electric vehicle; električna energija; električna vozila; emisije; emissions; global pollution; globalno onesnaževanje; internal combustion engine; motorji z notranjim zgorevanjem